THE INFLUENCE OF USER INTERFACE ON PURCHASING DECISIONS WITH BRAND IMAGE AS A MODERATING VARIABLE - Hermawan Hermawan; Efti Novita Sari; Erina Alimin; Mila Diana Sari; Muhamad Risal Tawil (ITB AAS Indonesia Surakarta, 2024)
This research is quantitative research with an exploratory approach, namely an approach that uses a number of previous studies as initial milestones for finding novelty and strengthening the research gaps that exist in this research. The data used in this research was distributed to 400 Owner of Madura Store spread throughout Indonesia. The questionnaire distributed contained 5 statements on 16 questions, namely strongly agree sentences, agree sentences, normal/average sentences, disagree sentences, and strongly disagree sentences. These data were analyzed using the smart PLS 4.0 analysis tool with the hypothesis below. The result in this article show the hypothesis which started from the researcher's assumptions, namely the User Interface variable, can have a positive relationship direction and a significant influence on Purchasing Decisions can be proven because the P-Values value is positive and is below the level the significance of 0.05 is 0.009. This can be caused by the simplicity of the system and the ease of product transactions, enabling consumers to immediately make purchasing decisions. Apart from that, the next column shows that the Brand Image variable can strengthen the influence of the User Interface variable on purchasing decisions because the P-Values value is positive and is below the significance level of 0.05, namely 0.000, which is more significant than the direct test of 0.009. Thus, it can be concluded that the first and second hypotheses in this research can be accepted and proven. Keywords: User Interface, Purchasing Decisions, Brand Image